Forensic Linguistics on Gender-Based Abuse and Harassment in Instagram Comments on Public Figures - Febri Pratomo Ramadhan Wijaya; Riyadi Santosa; Tri Wiratno (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines gender-based abuse and harassment directed at public figures in Instagram comment sections from a forensic linguistic perspective. Social media has expanded opportunities for direct public interaction, but it has also enabled verbal violence, hate speech, defamatory expressions, and gendered attacks to circulate rapidly. The study aims to identify the linguistic forms, meanings, and structural patterns of abusive comments and to explain their potential relevance to the analysis of language-related offences. A descriptive qualitative design was employed using Instagram comments and supporting online media reports as data sources. The comments were analyzed through Hallidayan transitivity, with attention to process types, participants, attributes, and circumstances. The findings show that abusive comments are predominantly constructed through attributive and identifying relational processes that assign degrading labels to an explicit or implied target. Recurring patterns include dehumanization through animal comparisons, body-shaming, sexualized and moral attacks, and insults based on gender identity or sexual orientation. Ellipsis of the copular process, accumulation of vulgar labels, capitalization, repeated letters, and exclamation marks intensify the aggression. Mental, verbal, and material processes also appear, particularly in expressions of anger, mockery, intimidation, and threat. These findings demonstrate that online abusive language is not linguistically neutral; rather, its grammatical organization constructs unequal power relations and normalizes verbal violence. Transitivity analysis therefore offers a systematic basis for documenting how insulting meanings are encoded and for supporting context-sensitive forensic interpretation.